Glutathione transferase activity and reduce glutathione content in the cytosol of rat gastric mucosa cells under carcinogen N-methyl-N'-nitro-Nnitrosoguanidine treatment - M.O. TymoshenkО, M.O. TymoshenkО, O.O. Kravchenko, L.M. Gaida, O.V. Lynchak, N.I. Ruzhytska, L.I. Ostapchenko O.O. Kravchenko, L.M. Gaida, O.V. Lynchak, N.I. Ruzhytska, L.I. Ostapchenko (Вiopolymers and Cell, 2012)
Aim. To determine the activity of glutathione transferase (GT) and the content of reduced glutathione (GSH) in the cytosol of the gastric mucosa cells in experimental gastrocarcinogenesis. Methods. The activity of GT was determined spectrophotometrically, the content of GSH was measured spectrofluorimetrically. Gastrocarcinogenesis was initiated by 10-week replacement of drinking water by 0.01 % solution of carcinogen N-methyl-N'-nitro-N-nitrosoguanidine, at the same time the rats were given a diet containing 5 % NaCl. Results. It was established that at the end of the 4th and 6th weeks of consumption of carcino- gen and NaCl, the activity of GT increased by 26 and 94 %, whereas the content of GSH increased by 135 and 85 %, respectively. After 12 weeks there was a decrease in the activity of GT by 50 % and the maximum decrease in the GSH concentration by 69 %. At the end of the 18th and 24th weeks it was recorded the increase in the activity of GT by 44 and 47 % and the decrease in the GSH content by 55 and 52 %. Conclusions. The changes in the activity of GT and GSH-content are evidence of the violation of glutathione homeostasis, which may cause the delay as well as initiation of development of the pathology. The reduction of GSH is established at the early stages of tumors formation.
Keywords: glutathione transferase, reduced glutathione, gastric cancer. Мета. Визначити глутатіонтрансферазну (ГТ) активність і вміст відновленого глутатіону (GSH) у цитозолі клітин слизової оболонки шлунка за умов експериментального гастроканцерогенезу. Методи. ГТ-активність визначали спектрофотометричним методом, вміст GSH – методом спектрофлуориметрії. Гастроканцерогенез ініціювали 10-тижневою заміною питної води на 0,01 %-й розчин канцеро- гену N-метил-N'-нітро-N-нітрозогуанідину з одночасним переведенням щурів на корм, який містить 5 % NaCl. Результати. По закінченні 4- і 6-тижневого споживання щурами канцерогену і NaCl ГТ-активність зростала відповідно на 26 і 94 %, тоді як вміст GSH – на 135 і 85 %. Через 12 тижнів спостерігали зниження активності ГТ на 50 % і максимальне зменшення концентрації GSH на 69 %. Після 18 і 24 тижнів зафіксовано зростання ГТ-активності на 44 і 47 % та зниження вмісту GSH на 55 і 52 %. Висновки. Зміни ГТ-активності і концентрації GSH свідчать про порушення глутатіонового гомеостазу, що може призводити як до затримки, так і ініціації розвитку патології. Встановлено зниження вмісту GSH на ранніх стадіях формування пухлин.
Ключові слова: глутатіонтрансфераза, відновлений глутатіон, рак шлунка. Цель. Определить глутатионтрансферазную (ГТ) активность и содержание восстановленного глутатиона (GSH) в цитозоле клеток слизистой оболочки желудка в условиях экспериментального гастроканцерогенеза. Методы. ГТ-активность определяли спектрофотометрическим методом, содержание GSH – методом спектрофлуориметрии. Гастроканцерогенез инициировали 10-недельной заменой питьевой воды на 0,01 %-й раствор канцерогена N-метил-N'-нитро-N-нитрозогуанидина с одновременным переводом крыс на корм, содержащий 5 % NaCl. Результаты. По окончании 4 и 6 недель потребления крысами канцерогена и NaCl ГТ-активность увеличилась соответственно на 26 и 94 %, тогда как содержание GSH – на 135 и 85 %. Через 12 недель наблюдали снижение ГТ-активности на 50 % и максимальное уменьшение концентрации GSH на 69 %. Спустя 18 и 24 недели зафиксировано возрастание активности ГТ на 44 и 47 %, а также снижение содержания GSH на 55 и 52 %. Выводы. Изменения ГТ- активности и концентрации GSH свидетельствуют о нарушении гомеостаза глутатиона, что может вызывать как задержку, так и инициацию развития патологии. Установлено снижение содержания GSH на ранних стадиях формирования опухолей.
Ключевые слова: глутатионтрансфераза, восстановленный глутатион, рак желудка.